Exploring The Dynamics : Analysis Of Income Tax Incentives, Earnings Management, Tax Avoidance, And Financial Distress Dynamics - Ranti Karlaili; Anisa Setyowati; Salsabila Andrina (Pusat Riset dan Inovasi Nasional, 2022)
This study delves into the interconnected dynamics of income tax incentives, earnings management, tax avoidance, and financial distress. The research aims to elucidate the relationships among these factors within the context of corporate finance. Employing a qualitative research design, the study utilizes purposive sampling to select participants with diverse experiences and perspectives in the realm of taxation and financial management. Data analysis entails thematic coding and pattern recognition to derive meaningful insights from interviews, documents, and archival records. The findings shed light on the nuanced strategies employed by firms to navigate the complexities of tax regulations, manage earnings, and mitigate financial distress. Moreover, the study highlights the implications of these practices for corporate governance and regulatory frameworks, offering valuable contributions to both academic literature and practical business management.